2017
DOI: 10.1111/nan.12426
|View full text |Cite
|
Sign up to set email alerts
|

Super‐resolution imaging of subcortical white matter using stochastic optical reconstruction microscopy (STORM) and super‐resolution optical fluctuation imaging (SOFI)

Abstract: Aims The spatial resolution of light microscopy is limited by the wavelength of visible light (the ‘diffraction limit’, approximately 250 nm). Resolution of sub-cellular structures, smaller than this limit, is possible with super resolution methods such as stochastic optical reconstruction microscopy (STORM) and super-resolution optical fluctuation imaging (SOFI). We aimed to resolve subcellular structures (axons, myelin sheaths and astrocytic processes) within intact white matter, using STORM and SOFI. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…To date, a single study reported STORM imaging on human brain tissue to visualize neuro laments, myelin and astroglial processes within subcortical white matter [22]. This study evidenced axonal diameters in the same range as our measurements and TEM values, highlighting the reliability and reproducibility of the technique.…”
Section: Discussionsupporting
confidence: 78%
“…To date, a single study reported STORM imaging on human brain tissue to visualize neuro laments, myelin and astroglial processes within subcortical white matter [22]. This study evidenced axonal diameters in the same range as our measurements and TEM values, highlighting the reliability and reproducibility of the technique.…”
Section: Discussionsupporting
confidence: 78%
“…For immunofluorescence, paraffin sections (6 μm thickness) were processed for labelling as in our previous work . Heat‐induced antigen retrieval was performed using a Menarini‐Biocare decloaker, (120°C, 30 sec, in citrate buffer pH6).…”
Section: Methodsmentioning
confidence: 99%
“…In the field of neuroscience, this new technique led to the characterization of the periodic structure of axonal cytoskeleton in neurons [7] and the spatial organization of synaptic proteins [8]. However, to date, STORM has mainly been used to image cultured cells and rodent brain samples [9].…”
Section: Introductionmentioning
confidence: 99%